LEGAL PROTECTION OF PATENT RIGHTS AS FIDUCIARY GUARANTEES IN BANKING CREDIT - I Gede Surya Winata; I Wayan Novy Purwanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
This study aims to identify and understand the legal protection of patents as fiduciary guarantees in bank credit and how to measure the economic value of patents as fiduciary guarantees. In addition, the study will investigate how to measure the legal protection of patents as fiduciary guarantees. This is a normative legal research using statutory approach, in this case Law Number 13 of 2016 concerning Patents and the Legal Concept Analysis Approach. This study includes primary legal material in the form of Law Number 42 of 1999 concerning Fiduciary Guarantees, Law Number 10 of 1998 concerning Banking as well as secondary legal material that is not binding but explains the primary legal material. The findings revealed that in granting credit, clearly there is a guarantee that must be given by the debtor to the creditor. Hence, for the purpose of guaranteeing credit, the form of guarantee that is most appropriate to use in this case is to use a fiduciary guarantee. Further, fiduciary guarantees are regulated in Law Number 42 of 1999 concerning Fiduciary Guarantees.